“Actually Changing Our Way of Being”: Transformative Organizing and Implications for Critical Community-Engaged Scholarship - May Lin (Social Sciences, 2023)
Because research alone cannot dismantle racial inequity, this article focuses on lessons for critical community-engaged scholarship (CCES) based on the Relationship-Centered Schools campaign of Californians for Justice (CFJ), an educational and racial justice youth organizing group. The campaign embraced transformative organizing—an approach to social change that encompasses reshaping oppressive institutions and healing trauma wounds wrought by injustice. I discuss findings and methodological implications for CCES, considering challenges in translating research to policy change for racial equity. This article situates the power and limitations of research within CFJ’s broad array of transformative organizing strategies to create more caring and equitable schools. Strategies include youth-led action research, voter engagement, lobbying, youth sharing power with adults, and healing practices of slowing down and relationship building to rehumanize youth of color. I then discuss implications for CCES. First, research supported CFJ youth leaders’ efforts to press institutions to value their full, emotionally complex humanity and legitimize their emotional knowledge. Yet because research is only one of many strategies for transformative change, fully participatory research is not always within organizing groups’ capacity. Thus, researchers can act more expansively by lending our time, energy, and labor to power building. Second, care and healing practices embodied by CFJ can inspire researchers to center relationship building and care as praxis and translate these lessons to transform the academy into a more equitable place. Ultimately, transformative organizing shows how CCES can extend beyond equitable research practices to include more liberatory ways of being, feeling, and acting towards justice.